Cambridge Essays on Education - Benson, Arthur Christopher, 1862-1925 (Salt Lake City, UT : Project Gutenberg, 2004)
"Cambridge Essays on Education" by Arthur Christopher Benson is a collection of essays focused on educational principles and reforms, edited in the early 20th century, specifically around the post-war period. The book emphasizes the need for thoughtful discourse on education amidst the surge of new educational practices and ideals during a time of significant social change, encouraging educators to reflect on the foundational aims of education beyond merely practical or contemporary issues. At the start of the volume, Benson outlines the intention behind the publication, which is to bring together experienced educators and thinkers to explore the deeper motivations for education. The opening also discusses the current state of education, championing a shift toward nurturing individual faculties and aptitudes rather than adhering strictly to traditional and obligatory subjects. Furthermore, it highlights concerns regarding the balance between classic education and the emerging focus on science and practicality in the curriculum. The introductory portion sets the stage for a comprehensive examination of various topics within the scope of education, such as the training of reason and imagination, and the incorporation of values in the educational discourse. (This is an automatically generated summary.)
The aim of educational reform, by J. L. Paton -- The training of the reason, by W. R. Inge -- The training of the imagination, by A. C. Benson -- Religion at school, by W. W. Vaughan -- Citizenship, by A. Mansbridge -- The place of literature in education, by N. Smith -- The place of science in education, by W. Bateson -- Athletics, by F. B. Malim -- The use of leisure, by J. H. Badley -- Preparation for practical life, by Sir J. D. McClure -- Teaching as a profession, by F. Roscoe.
Release date is 2004-09-28
E-text prepared by Ted Garvin, Leah Moser, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Education